Demand Elasticity and Distribution Impact: Simulation of the Impact of Paid Plastic Bag Taxes on Urban Consumption Patterns - Komang Adi Kurniawan Saputra; Rachmat Pramukty (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the demand elasticity and distributional impact of a paid plastic bag policy as an environmental tax instrument in urban Indonesia. Using a qualitative approach through multiple case studies, data were obtained from in-depth interviews, policy document analysis, and limited observations. The results indicate that consumer responses to this policy are uneven. Modern retail consumers exhibit relatively high demand elasticity, with a significant decrease in plastic bag use, while in traditional markets and low-income groups, demand tends to be inelastic due to social norms, business competition, and limited alternatives. From a distributional perspective, the policy has the potential to have regressive impacts if a compensation mechanism and the provision of affordable alternatives do not accompany it. Furthermore, there is a gap between policy design and implementation capacity at the regional level, leading to apparent compliance and variation in implementation. These findings confirm that the effectiveness of environmental taxes is influenced by institutional, equity, and behavioral factors, necessitating a more contextual and equitable policy design.